2010
DOI: 10.1016/j.jrurstud.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The structural disempowerment of Eastern European migrant farm workers in Norwegian agriculture

Abstract: a b s t r a c tSince the 2004 EU enlargement established one European common labour market, a large number of Eastern Europeans have taken up seasonal employment as hired farm workers in Norwegian agriculture. Much attention in the public has been given to the potential for 'social dumping' of these migrating workers, as they are considered prone to exploitation by farmers looking for cheap and docile labour, and subject to low-wages and poor labour conditions. In response to these threats, Norway implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 11 publications
3
102
0
10
Order By: Relevance
“…The research gap is in part due to the hidden nature of low-wage work in the countryside, and also the associated dominance of idyllic and bucolic representations of rurality (see for example, Halfacree, 1996). Recent publications within this journal, however, have begun to challenge sanitised constructions of rurality, and address the gaps within the literature with respect to rising low-wage immigration into rural areas (Findlay and McCollum, 2013;Hanson and Bell, 2007;Rye and Andrzejewska, 2010). The paper has contributed to this emerging literature through a specific focus on temporary migrant worker programmes (TMWPs) that are orientated towards migrant employment in the food industries of the developed world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research gap is in part due to the hidden nature of low-wage work in the countryside, and also the associated dominance of idyllic and bucolic representations of rurality (see for example, Halfacree, 1996). Recent publications within this journal, however, have begun to challenge sanitised constructions of rurality, and address the gaps within the literature with respect to rising low-wage immigration into rural areas (Findlay and McCollum, 2013;Hanson and Bell, 2007;Rye and Andrzejewska, 2010). The paper has contributed to this emerging literature through a specific focus on temporary migrant worker programmes (TMWPs) that are orientated towards migrant employment in the food industries of the developed world.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear, however, that developed world agriculture in particular has become increasingly reliant upon low-wage, but not necessarily low-skilled, migrant labour. Recent publications, especially within this journal, have demonstrated this point across a number of different national contexts (Findlay and McCollum, 2013;Hanson and Bell, 2007;Rye and Andrzejewska, 2010). In all cases the emphasis has been on the growing recruitment of seasonal migrant farm workers employed primarily within the fruit and vegetable (horticultural) sectors during harvest time.…”
Section: Introductionmentioning
confidence: 95%
“…In his study of housing conditions of migrant farmworkers in the United States, Larson (125) found that housing problems range from broken windows, lack of working shower and laundry facilities and broken toilets, to serious structural deficiencies, such as sagging roofs, porches or house frames, and each may contribute to concerns about poor health and safety . In this regard, studies show that poor housing conditions are one of the major factors that affect migrant farmworkers' health, leading to dissemination of various infectious skin diseases, respiratory diseases, infectious diseases and injuries (39,121,123,125,128,129,130). (130) United States, North Carolina Journal article, guided questionnaires, quantitative Deficiencies in basic services, such as medical care Accessing basic social services, such as medical care, was a problem that echoed in some manner in most of the literature we have reviewed (81, 94, 97, 98, 113, 128, 131--137).…”
Section: Methodsmentioning
confidence: 99%
“…For the workers, labour tasks are hard and monotonous (for example, harvesting vegetables or picking berries) and working hours are long. Wages are relatively poor by Norwegian standards, but good in terms of Eastern European standards (Rye and Andrzejewska 2010).…”
Section: Analysis Part 1: Circularity Of Farm Work Migrationmentioning
confidence: 97%
“…Even though some migrants admit that they feel a certain level of attachment to the place and to their employer -some even refer to the farmer's family as their 'second family' away from home -their frame of reference is predominantly that of their home country (Rye and Andrzejewska 2010). Moreover, when engaging in practices often seen as indicators of transnationalism (such as recruitment practices and use of new telecommunications) these strengthen their sense of belonging to their homeland community instead of leading to transnational cultural practices and hybrid identities.…”
Section: Lost In Transnational Space?mentioning
confidence: 99%